Ageing study of palm oil and coconut oil in the presence of insulation paper for transformers application - Mohamad N.A.; Azis N.; Jasni J.; Kadir M.Z.A.A.; Yunus R.; Yaakub Z. (MDPI AG, 2023)
Dielectric materials; Electric impedance measurement; Insulating materials; Oil shale; Thermal aging; Thermal insulation; Ageing temperature; Alternating current; Coconut oil; Dielectric dissipation factors; Insulation paper; Physico-chemical measurements; Refined , bleached , and deodorized; Relative permittivity; Palm oil